Business and Accounting Ethics in Islam - Muhammad Akram Khan (International Institute of Islamic Thought, 1992)
The present book represents the first serious attempt to explore Islamic business and accounting ethics. After placing their subject in a broad Islamic framework, which they have documented quite ably, they then compare the distinctive features of Islamic business and accounting principles with Western theory and practice. While the book has several strong points and breaks new ground in a number of areas, it also lacks clarity and specific authority from Islamic sources on quite a few points. To begin with, the authors argue quite convincingly that the logical corollary of prohibiting riba (interest) is the negation of any time value for money. Thus the theory and practice of capital budgeting, which feature in the use discounted cash flow techniques in the West, become redundant. This point, seemingly so obvious to economists, has not found favor with the economic thinking of the Islamic establishment. Rather, many Muslim economists and accountants have been busy justifying it on one pretext or another. This is the fitst time that somebody has come out with a compelling discussion of this question. The authos have also argued that Islam absolutely forbids the nonrepayment of a debt. Thus the concept of limited liability, one of mainsprings of economic power in a capitalist society, is not recognized by Islam. However, the related theory of incorporation, the legal mechanism for justifying limited liability, is found in Islamic societies. Again, such an obvious and sensible point remains unacceptable to Muslim economists. They continue looking for excuses to accept these ideas, thereby betraying their intellectual poverty. Although the authors do not devote a single chapter to the state’s economic role in Islam, they discuss this question throughout the book They argue for a strong regulatory and framework role for the Islamic state. Gambling and Abdel Karim deal with several other important issues. For instance, they argue that the Islamic concept of economic development revolves around the development of human resources rather than capital formation, as is the main focus of the popular theory of development in the West. In their discussion of the Islamic concept of shura (consultation) and khilafa (vice-gerency), they also bteak new ground. They opine that these concepts question ...